SÃO PAULO, CIDADE PUNK: PRÁTICAS, ESPAÇOS, REPRESENTAÇÕES (1982-1998) - Silva, Andre Abreu da (2016)
This is a Historical narrative and inquiry about São Paulo city, underneath the punk culture perspective. We notice, measurably, the uses, the making, the ways of apropriation and the representations of the urban space on the punk cultural stuff and experiences, into the materiality of São Paulo from 1982 to 1998. Punks, congregate in these context as a youth crew of political and culture activism from the suburbs and outskirts, which produced a compilation of dialectical images about the city. This last one known, among other features, as a space of production and assimilation of representations. We work the Historical inquiry by the analysis of the punk culture stuff kept archived: posters, handouts, magazines, pictures, musical recordings, and more. The redemption of the representations and the ways of assimilation of São Paulo‟s urban space by the punks showed us features, dimensions and hidden temporalities of the city. Protagonists that collaborate not only in the everyday paths‟ formation, but, essentially, in the political critical intervention, in the antagonizing culture, and daring overtake symbolical and physical borders and boundaries determinate by the Establishment.